Effects of Motivation, Knowledge, and Skills of Lung Tuberculosis Officers on Case Detection Rate of Health Centers - Margareta Suhanika Purnaningsih; Elsa Pudji Setiawati; Kuswandewi Mutyara (Faculty of Medicine, Public Health, and Nursing, 2022)
Background: One of the main indicators of tuberculosis prevention is the Case Detection Rate (CDR). The CDR of health centers in East Lampung Regency in 2017 was 24.8% which is still below the national standard. Case finding was still being done passively and suspect screening in several health centers was found lacking attention to the patient's medical history. Accordingly, increasing CDR needs improvement efforts to be strongly influenced by tuberculosis officers.Objectives: This study aimed to determine the effects of motivation, knowledge and skills of tuberculosis Officers on CDRs of community health centers in East Lampung Regency.Methods: This study is a cross-sectional quantitative study with total sampling. Data were obtained from questionnaires, checklists and secondary data from community health centers and East Lampung District Health Office. Respondents are 34 community health centers in Lampung Timur represented by 89 officers. Dependent variable was CDR while motivation, knowledge, and skills were the independent variables. The data were analyzed by Rank Spearman tests and multiple linear regression methods.Results: Respondents showed they were lacking in motivation, good knowledge and skills. Rank Spearman correlation coefficient ranged between 0.665 to 0.696 with sig.=0,000. Regression sig values were 0.000 for motivation, 0.0962 for knowledge and 0.001 for skills. Adjusted R square was 0.703, while regression coefficient was 2.872 for motivation and 1.196 for skills.Conclusion: There were significant correlations between motivation, knowledge and skills with CSRs of community health centers in East Lampung Regency. Knowledge had no effect on CSR but motivation and skills have a significant effect partially and simultaneously. Motivation contributed the biggest effect.